Ekstraksi Kulit Jeruk Manis (Citrus Sinensis) Sebagai Bahan Aditif Pembuatan Lilin Aromaterapi Berbahan Baku Minyak Kedelai (Soy Wax) - M. Riski Syahputra; Elwina Elwina; Fachraniah Fachraniah (Jurnal Teknologi, 2026)
This study aims to utilize sweet orange peel (Citrus sinensis) as an additive in the production of aromatherapy candles based on soy wax. Essential oil extraction was carried out using the maceration method with 96% ethanol as the solvent. The independent variables in this study included variations in the volume of orange peel extract (2–6 mL) and the mass of soy wax (100–300 g), while the dependent variables comprised pH measurement, melting point analysis, component analysis using gas chromatography–mass spectrometry (GC–MS), and organoleptic evaluation (aroma, shape, and color). The results showed that the orange peel extract yielded essential oil with a fresh citrus aroma and a pH ranging from 5.5 to 5.8. The melting point of the candles increased with increasing extract volume and soy wax mass, reaching a maximum temperature of 54°C. The best burning resistance was obtained at the combination of 250 g soy wax and 6 mL extract, with a burning duration of 4.49 hours. Hedonic testing indicated the highest aroma preference at the combinations of 100 g soy wax with 6 mL extract and 300 g soy wax with 5 mL extract, with a hedonic score of 4.93. GC–MS analysis revealed that the major components of the essential oil were D-limonene, linalool, and other alcohol compounds, which contribute to relaxation effects and a characteristic citrus aroma. Overall, the findings demonstrate that sweet orange peel extract has strong potential as a natural additive in the production of environmentally friendly and economically valuable aromatherapy candles.